2020
DOI: 10.3390/nu12123849
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Micronutrients, Lutein, and Docosahexaenoic Acid Supplementation during Lactation: A Randomized Controlled Trial

Abstract: Breastfed infants require an adequate supply of critical nutrients for growth, tissue functions, and health. Recommended intakes for several nutrients are considerably higher in lactating than non-lactating women but are not always met with habitual diets. We report a randomized, double-blind clinical trial in 70 healthy lactating women in Germany evaluating the effects of supplementation with multiple micronutrients, lutein, and docosahexaenoic acid (DHA) compared to placebo on maternal nutrient status and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
1
9
1
3
Order By: Relevance
“…Although the study was performed in a country with a high standard of living, the dietary intake of macro-and micronutrients was often inadequate. The study authors emphasise that supplementation preserves DHA levels in breast milk and state that this may lead to clinical benefits for the infant [3]. However, the present study did not investigate such possible clinical benefits.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Although the study was performed in a country with a high standard of living, the dietary intake of macro-and micronutrients was often inadequate. The study authors emphasise that supplementation preserves DHA levels in breast milk and state that this may lead to clinical benefits for the infant [3]. However, the present study did not investigate such possible clinical benefits.…”
Section: Discussionmentioning
confidence: 74%
“…The recommended intake for crucial nutrients, for example iodine, is considerably higher in lactating than in nonlactating women [2,3]. Even in countries with a high standard of living, multiple micronutrient deficiencies are widespread [3].…”
Section: Micronutrient Intake By Lactating Mothers Often Insufficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of DHA status has been widely focused on because of application of n -3 FA supplementation in functional food [ 37 ] and the management and treatment of diseases [ 38 , 39 ]. In this study, we observed a significant positive correlation between plasma and erythrocyte DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve weeks supplementation of breastfeeding mothers with a multiple micronutrient supplement containing very low amounts of lutein (250 ug/day) vs. placebo was found to to prevent the decline in maternal plasma of lutein concentrations. Furthermore, while a decrease in lutein levels in breast milk during lactation was observed in mothers supplemented with placebo, no decrease was observed in the group receiving low dose lutein [ 116 ].…”
Section: Lutein In Pregnancy and Breastfeedingmentioning
confidence: 99%